Relationship between Syntax I - Syntax II and Spielberger State-Trait Anxiety Inventory in stable angina pectoris patients - Çelik, Mustafa (Journal of Surgery and Medicine, 2020)
Aim: State-trait anxiety inventory (STAI) is a parameter used to measure anxiety levels. SYNTAX score is an anatomically based scoring system used to determine the complexity of coronary artery disease (CAD). We investigated the relationship between SYNTAX-I, SYNTAX-II scores, and STAI. Methods: A questionnaire-based cross-sectional study was conducted on 150 consecutive patients (54 female and 96 male) who presented to our hospital with the diagnosis of stable angina pectoris and underwent elective coronary angiography (CAG). Patients answered the STAI questionnaire at least 1 hour prior to elective CAG. Assessment of the cineangiographic images was performed by two experienced cardiologists blinded to the study data. Results: The evaluation of Spearman’s Rho correlation coefficients revealed a significant, strong, and positive relationship between STAI score and SYNTAX I (r=0.757, P<0.001), as well as SYNTAX II (r=0.811, P<0.001). SYNTAX I and SYNTAX II scores were also significantly positively correlated (r=0.681, P<0.001). Conclusion: We found a strong and significant correlation between SYNTAX I, SYNTAX II and STAI score variables. STAI score level is an independent and strong predictor of SYNTAX score and can be used a pretest indicator to identify patients with CAD.